Market-type Mechanisms and the Provision of Public Services - Blöndal, Jón R.. (OECD Publishing, 2006)
Market-type mechanisms are defined as "encompassing all arrangements where at least one significant characteristic of markets is present." In the area of service provision, the prime instruments include outsourcing (contracting out), publicprivate partnerships (PPPs) and vouchers. This article describes each instrument, surveys its use in OECD countries, analyses the key issues involved, and offers an overall assessment